Transient natural convection in an enclosure filled with a saturated porous medium - Merrikh, Ali Akbar; Pop, Ioan Mihai; Mohamad, Abdulmajeed Abd (Begell House Inc. orders@begellhouse.com, 1997)
Transient convective flow in an enclosure filled with a saturated porous medium is investigated using Darcy-Boussinesq approximation. The flow is driven because of the temperature difference between the vertical walls of the enclosure where the horizontal walls are assumed adiabatic. A second order accurate in time and in space, MacCormack scheme, is used for the numerical solution of the time dependent energy equation. The present analysis is performed for Rayleigh numbers in the range 1-1000 and aspect ratios 1 and 2. Grid and time independence is carefully tested and flow structure and heat transfer characteristics are presented for the above ranges of parameters. It was observed that there is a certain time needed for the flow to reach the cold side wall and this time period was found to be dependent on aspect ratio and Rayleigh number parameters. Also it was observed that as aspect ratio increases, the time to achieve steady state increases. © 1997, Begell House Inc. All rights reserved.
International Symposium on Advances in Computational Heat Transfer, CHT 1997 -- 1997-05-26 through 1997-05-30 -- Çeşme -- 224419
Keywords: Enclosure; Natural convection; Porous media; Transient